High Performance Network Worm Detection Engine Using Memory Efficient Circular Buffer. - Budiarto, Rahmat; Ramadass, Sureswaran; Pasha, Muhammad Fermi; Manasrah, Ahmad; Supramaniam, Saravanesh (2007)
This paper presents the implementation of a memory efficient circular buffer to ensure a high performance network worm detection engine. A worm detection engine's primary function is to detect the existence of worms in a particular network.